Women in Science and Technology in Higher Education in Ghana: Policy Environments and Experiences - Wurah-Norgbey, Enyonam (Université d'Ottawa / University of Ottawa, 2019)
In the current era of globalization, knowledge-based innovations are critical for socio-economic development. In most African countries, however, the level of African-based research and development is minuscule. In addition, there continues to be a considerable gender gap in higher education throughout Africa, where male enrolments far outweigh female enrolments, particularly in the science and technology (S&T) fields. This gender discrepancy has raised concerns about the factors that underlie reduced female enrolment in S&T programs in African universities. Equally intriguing, in view of the relative scarcity of women in the S&T fields, there is surprisingly little knowledge concerning the attributes and the experiences of those African women who do enrol and teach in S&T fields, and who thus can serve as role models for younger girls who have an interest or the potential for pursuing studies in these fields. In Ghana, although policy initiatives have been undertaken to increase women’s participation in higher education, women remain underrepresented in science and technology (S&T) fields, particularly, at the graduate education level. To gain a better understanding of how some women have overcome longstanding obstacles to gender equality in S&T, my dissertation focused on the evolving status of 24 African women in three S&T graduate education programs – Africa Centres of Excellence (ACE) – in two universities in Ghana. To shed light on the factors that facilitate or hinder women’s participation in S&T graduate programs, a qualitative inquiry, into the experiences and perceptions of these women was undertaken. The conceptual framework presents the sequence of three approaches: (a) advocacy to raise consciousness about underlying gender-disparity issues; (b) a gender-affirmative-action approach to recruit and train a critical mass of female scientists and researchers; and (c) promotion of gender mainstreaming as a way of bringing gender perspectives into the universities’ cultures. This framework has been complemented by the structuration theory that has been useful in illuminating the experiences and perceptions of the women in the S&T ACE graduate programs in Ghana. These conceptual and theoretical frameworks have helped elucidate how the development and effective implementation of gender policies and procedures can lead to the transformation of institutional, social and global structures. Structures in turn can impact women’s agency and help overcome gender disparity in S&T higher education. The analysis of the women’s stories provided insights into the intersection of gender, socio-cultural factors, organizational cultures, and how gendered challenges impacted the professional aspirations of the women academics in the two public universities studied in Ghana. Beyond a better understanding of women’s experiences, this study helps us understand gender inequalities and the societal norms and practices, as well as patriarchal forces that permeate societies and impose structural barriers to women’s advancement. The study also helps to address a major research gap concerning the forces that affect, for better or worse, women’s experiences and potential academic contributions in S&T in Ghana and elsewhere in the world and adds to the broader literature on women’s experiences in male-dominated fields.
Keywords: Gender; Education; Science; Technology; Ghana; Higher; Structuration; Policy